The percentage and sequence of performing basic measures of newborn care in the delivery or operating room in Khorasan Razavi hospitals during 2021-2022 - Maryam Zakarihamidi; Samira Mahmoudi; Malihe Mohseninia; Maryam Azari Azghandi; Nahid Sorgi; Fatemeh Bagheri; Maryam Moradi; Hassan Boskabadi (Mashhad University of Medical Sciences, 2023)
Introduction: The "golden hour" concept is a new evolving strategy for better prognosis of preterm and term infants, and all health care providers should be informed about the components and importance of the golden hour approach. The present study was performed with aim to investigate the percentage and sequence of primary care measures for newborns in the delivery or operating rooms in Khorasan Razavi hospitals. Methods: This descriptive study was conducted in 2021-2022 on 1286 babies born in the maternity ward and operating room in Khorasan Razavi public hospitals. The percentage and sequence of taking care of newborns were investigated immediately after birth. Data were analyzed by SPSS software (version 26) and Statistical indices. P< 0.05 was considered statistically significant. Results: Drying and warming in 98%, making skin to skin contact of the baby with the mother's breast in 65%, positioning in 61%, emptying mouth secretions and stimulating the baby in 41%, putting on a hat in 61%, controlling the number Breathing in 48%, heart rate in 38% and temperature check in 25% were done among babies. The summary of the order of care measures performed for newborns was: tying the umbilical cord, starting skin-to-skin contact, drying, warming, stimulating, emptying mouth secretions, putting on a hat, determination of first minute Apgar, weight control, height control, head circumference control, determination of fifth minute Apgar, first respiratory rate control, first pulse rate control, first breastfeeding, body temperature control, foot impressions, vitamin K injection, diapering, and transfer to obstetrics department. Conclusion: In maternity wards and operating room of Khorasan Razavi public hospitals, essential measures such as vital signs are evaluated in less than half of the babies, and the order of care is not appropriate. Therefore, the modification and training of the neonates' care worker needs a serious revision and it is necessary for the health care workers to review the care and order of their performance.